2015
DOI: 10.1007/s11664-015-3855-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of Surface and Interface Roughness of GaN-Based Films Using Spectral Reflectance Measurements

Abstract: GaN films were grown using SiN treatment of sapphire substrate by metalorganic vapor-phase epitaxy in a home-made vertical reactor at atmospheric pressure. The growth was interrupted at different stages to investigate the impact of interface and surface roughness on the optical properties of the GaN layers. A transition from a three-dimensional (3D) to two-dimensional (2D) growth mode was revealed by real-time in situ laser reflectometry (k = 632.8 nm) as well as by atomic force microscopy images. A theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Consequently, it was experimentally found that the saturation of photocurrent increased around three times higher in the truncated nanocones compared to the planar GaN with a high incident photon to electron efficiency and charge transfer rate. In conclusion, the optimum truncated nanocone provides higher photocatalytic efficiency than the existing planar GaN-based water splitting by the only surface texturing without huge structural modification in the conventional system . Furthermore, our proposed geometries with light trapping properties can also be applicable to GaN based photocatalytic materials.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consequently, it was experimentally found that the saturation of photocurrent increased around three times higher in the truncated nanocones compared to the planar GaN with a high incident photon to electron efficiency and charge transfer rate. In conclusion, the optimum truncated nanocone provides higher photocatalytic efficiency than the existing planar GaN-based water splitting by the only surface texturing without huge structural modification in the conventional system . Furthermore, our proposed geometries with light trapping properties can also be applicable to GaN based photocatalytic materials.…”
Section: Discussionmentioning
confidence: 85%
“…In conclusion, the optimum truncated nanocone provides higher photocatalytic efficiency than the existing planar GaNbased water splitting by the only surface texturing without huge structural modification in the conventional system. 33 Furthermore, our proposed geometries with light trapping properties can also be applicable to GaN based photocatalytic materials. We believe our approach will pave a new way to improve the water splitting efficiency.…”
Section: ■ Conclusionmentioning
confidence: 93%
“…First, we utilized wet chemical etching to selectively create macropores on the GaN surface (e-GaN) based on the solvothermal treatment in KOH solution without any metal catalyst, followed by its heterojunction with MoS 2 , MoSe 2 , and MoSe 2 /MoS 2 using a simple spray coating technique. The introduction of macropores to the GaN surface enhances the optical absorption 100 times, significantly improving the light–matter interaction and facilitating the PD performance. , Interestingly, compared to single heterojunction devices, the double heterojunctions that maintained staircase-like (type-II) band alignment established better photodetection performance. The optimized heterostructure exhibits a very high photoresponsivity of 82 A/W, specific detectivity of 1.79 ×10 14 Jones, external quantum efficiency of 27,880%, and stability for over 6 months in a laboratory testing environment under the illumination of 365 nm, with an intensity of 150 nW/cm 2 and bias of 3 V. Further, DFT simulations support better charge separation and transport mechanisms for the e-GaN/MoSe 2 /MoS 2 -based hybrid 2D/3D heterostructures in terms of electron localization function and transport probability.…”
Section: Introductionmentioning
confidence: 99%